A Bibliometric Analysis of Educational Games to Teach Cultural Diversity in Elementary Schools - Pranata, Alvira; Syamsijulianto, Tri (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
The research trend regarding educational game-based learning media introducing cultural diversity in elementary schools has increased recently. The integration of culture-based games is an innovative approach in the field of teaching especially in addressing cultural diversity in educational settings. This trend stems from recognizing the importance of promoting cultural awareness, understanding, and acceptance among students from an early age. This research is bibliometric. We collected several articles about ethnoscience and educational games from the Semantic Scholar database published from 2012 to 2023. Overall, harnessing the power of educational games in elementary schools can effectively engage students in meaningful cultural learning experiences that promote empathy, respect, and global citizenship from an early age.